Prognostic Nutritional Index Predicts Outcomes of Patients after Gastrectomy for Cancer: A Systematic Review and Meta-Analysis of Nonrandomized Studies. (19th May 2019) - Li, Jian; Xu, Run; Hu, Deng-Min; Zhang, Yao; Gong, Tu-Ping; Wu, Xue-Lian
Abstract: Objective: The primary aim of this systematic review was to evaluate the survival predication value of preoperative prognostic nutritional index (PNI) in patients with gastric cancer. The second aim was to explore the relationship between preoperative PNI and clinicopathological features. Methods: A systematic search of the electronic databases identified studies that investigated the association of preoperative PNI with short or long-term outcomes among patients after gastrectomy for cancer. Qualitative and quantitative analysis of results was conducted. Results: Twenty-five studies with a total of 14, 403 patients with gastric cancer met inclusion criteria for this review. Pooled analysis demonstrated that low preoperative PNI was associated with significantly reduced overall survival (HR 1.81, 95% CI: 1.56–2.09; P = 0.000), cancer-specific survival (HR 1.61, 95% CI: 1.24–2.10; P = 0.000), and recurrence-free survival (HR 1.82, 95% CI: 1.20–2.77; P = 0.005). In addition, risk of postoperative complications (POCs) and mortality was significantly higher in patients with lower preoperative PNI (RR 1.77, 95% CI: 1.44–2.17; P = 0.000 and RR 5.14, 95% CI: 2.23–11.79; P = 0.000, respectively). Conclusion: This study suggests that patients with low preoperative PNI may have a high incidence of POCs and poor prognosis following gastrectomy for cancer.